2019
DOI: 10.1016/j.apsusc.2018.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray photoelectron spectroscopy investigation of annealing effects on buried oxide in GaAs/Si junctions by surface-activated bonding

Abstract: Hard x-ray photoelectron spectroscopy measurements are performed on ≈10-nm-thick GaAs film/Si substrate junctions fabricated by the surface activated bonding and selective wet etching. The chemical shifts of Ga-O and As-O signals in Ga 2p 3/2 and As 2p 3/2 core spectra indicate that oxides are formed in a part of GaAs films neighboring GaAs/Si interfaces due to the surface activation process. Analyses of Ga-O and As-O signals show that the thickness of such buried oxides is decreased due to a post-bonding anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…The crystal defect layer formed at the GaAs/diamond bonding interface is unlike the previous reports that there was an amorphous layer formed at the Si/Si [20], Si/GaAs [21], Ge/Ge [22], and Si/SiC [23] interfaces fabricated by SAB. On the other hand, a crystal defect layer formed at the GaAs/GaAs interface fabricated by SAB has been reported [24].…”
Section: Discussioncontrasting
confidence: 77%
“…The crystal defect layer formed at the GaAs/diamond bonding interface is unlike the previous reports that there was an amorphous layer formed at the Si/Si [20], Si/GaAs [21], Ge/Ge [22], and Si/SiC [23] interfaces fabricated by SAB. On the other hand, a crystal defect layer formed at the GaAs/GaAs interface fabricated by SAB has been reported [24].…”
Section: Discussioncontrasting
confidence: 77%
“…After annealing at 700 °C, the crystal defect layer was recovered, so the structure of the composite layer could be recognized. The recovery of the crystal defect layer was very similar to the findings in previous reports, indicating that the damaged layer formed at the interface by Ar beam irradiation can be recrystallized through a high-temperature annealing process. ,, …”
Section: Resultssupporting
confidence: 88%
“…The recovery of the crystal defect layer was very similar to the findings in previous reports, indicating that the damaged layer formed at the interface by Ar beam irradiation can be recrystallized through a high-temperature annealing process. 35,37,38 The thermal expansion coefficient of the composite layer composed of Cu and diamond should be different from those of the bulk diamond and Cu. It has been reported that the thermal expansion coefficient of the composite material composed of Cu and diamond highly depends on the component ratio between diamond and Cu, decreasing with increasing amounts of the diamond component.…”
Section: Uncertainties Of Tbr (mentioning
confidence: 99%
“…[46] Similar properties were observed in SAB-fabricated GaAs/Si, GaP/GaAs, and GaSb/GaInP interfaces. [47][48][49] The diffusion of Ga and N atoms is much more likely to occur in amorphous carbon than in diamond due to the former's low atomic density. [50] No diffusion of Ga or N atoms into the diamond substrate adjacent to the intermediate layer was observed even after annealing at 1000 °C, while the C atom diffused into the GaN after annealing at 700 °C.…”
Section: Resultsmentioning
confidence: 99%